A 2.5 GHz broadband balanced amplifier with gain margin and gain flatness tuning capability - Ali H. Ramadan (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2025)
In this paper, the S-parameters of a balanced topology that employs two identical branch amplifiers are formulated and evaluated for a 2.5 GHz broadband amplifier. A prototype is fabricated and measured to validate the performance of the designed amplifier, where a good agreement between simulated and measured results is noticed as follows. |S11| and |S22| are less than -13 dB over 2.5 GHz ± 5 % and reveal a broadband operation for the balanced amplifier. |S12| is below -20 dB over the 1.5–3.5 GHz frequency span, whereas |S21| has a value around 12.4 dB at 2.5 GHz. The noise figure, output 1dB compression point, and output third-order intercept point of the designed amplifier are found to be NF=1.3dB, OP1dB≈1dBm, and OIP3≈17.5dBm, respectively. Additionally, a 60.6dB distortion of 3rd order harmonics is attained. The versatile gain margin and gain flatness tuning attributes of a balanced amplifier topology are then looked into through a parametric study that accounts for tuning the values of CS and LL of the incorporated GS (LC) and GL (series-L) matching blocks in individual and dual manners. The tuning process reveals that the gain margin can span from 9.75 dB to 14.65 dB with various gain flatness intervals over 2.5 GHz ± 5 %, and therefore promotes the candidacy of balanced amplifiers for use in applications where gain margin and/or gain flatness adjustment over broad frequency bands is demanding.